Analisis Kelayakan Anggota Dalam Pembiayaan Qardh Bisyarti Rahni di KSPPS-BMT Lima Satu Cabang Kedung - Anggisna Laila Nurrahmawati; Ahmad Fauzan Mubarok; Zahrotun Nafisah (Jurnal Ilmiah Ekonomi Islam, 2025)
This study aims to analyze the eligibility of members in Qardh Bisyarti Rahni financing at KSPPS BMT Lima Satu Kedung Branch using the 6C assessment (Character, Capacity, Capital, Collateral, Condition of economy and Compliance). The research method used is descriptive qualitative, with data collection through in-depth interviews, documentation, and direct observation. The results of the study indicate that the eligibility of members in this financing is influenced by several factors, including financial capacity, previous financing history, and members' commitment to sharia principles that avoid usury, gharar and maysir. BMT Lima Satu not only provides funds effectively to support the utilization of financing by members. In addition, this institution implements strict procedures to ensure compliance with sharia principles. This research is expected to contribute to the development of more effective and efficient sharia financing products in the future, as well as improving the welfare of members through responsible financing access.